Bias Gender dalam Tafsir: Kritik atas Dalil dan Pandangan Misoginis Terhadap Kemandulan Perempuan - Nur Azny Agustina Putri (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2023)
In the Quran, the term infertility is expressed with the words 'āqir and 'aqīm. The word 'āqir is used to describe the condition of barrenness experienced by the wife of Prophet Zakariya. While lafadz 'aqīm is used to explain the condition of infertility experienced by the wife of Prophet Ibrahim. The scholars have different opinions in interpreting these two words. Some of them define both of them as sterility which is a special condition for women so that the woman cannot become pregnant. These arguments about infertility need to be studied in depth because they contradict one of the visions of Islam that teaches equality. It is not the text that is wrong, but human understanding of a proposition that needs to be straightened out. In studying the verses about infertility, the researcher uses the qirā`ah mubādalah approach by understanding the verses of the Qur'an through universal texts, finding the main idea or moral ideal of a verse and implementing the main idea to the verse. Implementing the main idea to a general subject without distinguishing gender and sex. The results show that 'āqir is sterility that can happen to anyone regardless of gender. The cause of 'āqir is the presence of certain factors that prevent pregnancy.  If these factors are removed, then pregnancy can occur. Whereas 'aqīm is sterility that can happen to anyone regardless of gender. Unlike 'āqir, 'aqīm is sterility that is known from the beginning, because it is created that way. Therefore, attributing 'āqir and 'aqīm only to women is a gender-biased understanding, because sterility can be caused by anyone, regardless of gender. This kind of understanding needs to be developed to produce egalitarian values in the midst of society.